Isolasi Khitin dari Cangkang Rajungan (Portunus pelagicus) kajian Suhu dan Waktu Proses Deproteinasi - Martati, Erryana; Susanto, Tri; Yunianta, Yunianta; Ulifah, Ida Ayu (Jurnal Teknologi Pertanian, 2002)
The aim of  research was to study the effect of temperature and the time exposure of deproteinization toward chitin characteristic. This experiment was done in various temperature i.e.  65, 75 and 85 0C and time exposure i.e. 2, 6 and 10 hours. The results showed the temperature treatment had influence toward degree deacetylization, nitrogen content and the yield very significantly. The time exposure treatment had influence toward degree deacetylization and nitrogen content very significantly. Interaction between two kinds of treatment had influence only toward degree deacetylization. The best treatment was selected by Multiple Attribute Method. It was deproteinization at 750C for 6 hours, result in nitrogen content 4,58%, degree deacetylization 12,14%, water content  4,41%, ash content 1,07% and the yield  14,57%. That chitin fulfilled chitin standard.   Key words : chitin, deproteinization, crab shell